Sinesio de Cirene, intelectual. La escuela de Hypatia en Alejandría - Blázquez Martínez, José María (Gerión. Revista de Historia Antigua, 2005)
Synesius of Cyrene (370-413) is a good example of a rich intelectual who comes to be bishop. The first education he received in his town. Later on frequented some years in the Academy of Hypatia at Alexandria, that was one of the most important academies in this moment. Hypatia teached neoplatonism for her students, mathematics, geometry and occult sciences. In this academy students were formed to get highest magistracies of the Empire. Synesius was an intelectual, delivered to the philosophy, a good dipiomatic, good warrior and huntsman and bishop at Ptolemais. Hypatia was cruelly murdered by the christians.
Keywords: Synesius of Cyrene; Hypatia; neoplatonism; Alexandria; bishop; huntsman; warrior